Cassava Annual Report 2020 - Becerra-Lopez Lavalle, Luis Augusto; Newby, Jonathan Craig; Zhang, Xiaofei; Bohorquez-Chaux, Adriana; Malik, Imran; Cuéllar, Wilmer Jose; Delaquis, Erik; Slavchevska, Vanya; Tran, Thierry; Chavarriaga, Paul; Escobar Pérez, Roosevelt Humberto (2021)
Cassava cultivation, though labor intensive and often subsistence oriented, provides smallholders and landless farmers as well as processors and traders across the tropics with a vital entry point for creating employment and income. Outperforming other crops in poor soils and under unpredictable rainfall, cassava is also crucial for enhancing the resilience of crop production systems in the face of climate change. However, cassava will become more susceptible to pests and diseases, as climate change likely increases their range of mobility. Moreover, production costs and postharvest losses remain high; technology uptake is limited; and producers’ market links are weak, even though cassava serves as a feedstock for numerous industrial uses, including food, feed, and starch. The newly formed Alliance of Bioversity International and the International Center for Tropical Agriculture (CIAT) recognizes the vital contribution that cassava makes to poverty reduction, and this is reflected in the objectives and outcomes of the Cassava Sub-Lever’s recently developed strategy. In addition, we have prepared a multidisciplinary workplan across our six strategic Research and Service Areas (RSAs). The RSAs help integrate work on cassava with the Alliance’s strategy and lever structure, and also provide us with an overarching framework for prioritizing investments and delivering impacts in Latin America and the Caribbean (LAC )and Southeast Asia (SEA), while supporting the work of the International Institute of Tropical Agriculture (IITA) in sub-Saharan Africa. Guided by this strategic framework, the Cassava Sub-Lever relies on multiple strengths to fulfill its mission of improving the livelihoods of smallholder farmers through genetic solutions to global problems that are fit for purpose within agricultural-economic-social-ecological systems. In operational terms, the RSAs create logical groupings of work around key themes and areas of expertise. In the sections that follow, we report on some of the noteworthy results that the Cassava Sub-Lever achieved in 2020 through its six RSAs.